展開(-1-x)(-1+x)=?
回答 (3)
✔ 最佳答案
您好,我是 lop,高興能解答您的問題。
(1)
展開 (-1-x)(-1+x)
記住 (x-y)(x+y) = x²- y²,
所以
(-1-x)(-1+x)
= [(-1)+(x)][(-1)-(x)]
= (-1)²- x²
= 1 - x²
(2)
因式分解 1-x^2
記住 x²- y²= (x-y)(x+y) ,
1 - x²
= 1²- x²
= (1+x)(1-x)
參考: Hope I Can Help You ^_^ ( From me )
(-1-x)(-1+x)=(-1)^2-x^2=1-x^2
1-x^2=1^2-x^2=(1+x)(1-x)
參考: me
(-1-x)(-1+x)
=-1^2-x^2
=1-x^2
formula: a^2-b^2=(a-b)(a+b)
參考: meeeee^^
收錄日期: 2021-04-13 18:14:57
原文連結 [永久失效]:
https://hk.answers.yahoo.com/question/index?qid=20110913000051KK00829
檢視 Wayback Machine 備份